Please ANSWER THIS QUESTIONS BELOW ASAP

1. Verify that -2 is a zero of the polynomial p(a)=a+2 

2. Find the zero of the polynomial p(b)=b+10 

3. Factorise (b-c)3 +(c-d)33+(d-b)3 

4. Expand the following 
(i) (4a-b+2c)2 
(ii) (-x+2y-3z)2

5. Factorize the following 
(i) x2+9x+18 
(ii)2x3-3x2-17x+30
(iii) 9x2+4y2+16z2+12xy-16yz-24xz 
(iv) 1-64x2 

6. Simplify (2x-5y)3-(2x+5y)3 

7. Prove that (a+b+c)3-a3-b3-c3= 3(a+b)(b+c)(c+a)

Asked by prakash.sanyasi | 19th Aug, 2019, 02:25: PM

Expert Answer:

1. p(a) = a + 2
Put a = -2
p(-2) = -2 + 2 = 0
Hence, -2 is the zero of the given polynomial.

Answered by Sneha shidid | 19th Aug, 2019, 02:40: PM